Timed barium esophagram in achalasia types. Issue 4 (1st June 2015) - Zanoni, A.; Rice, T. W.; Lopez, R.; Birgisson, S.; Shay, S. S.; Thota, P. N.; Baker, M. E.; Raymond, D. P.; Blackstone, E. H.
Summary: Relationships of timed barium esophagram (TBE) findings to achalasia types defined by high-resolution manometry (HRM) have not been elucidated. Therefore, we correlated preoperative TBE and HRM measurements in achalasia types and related these to patient symptoms and prior treatments. From 2006 to 2013, 248 achalasia patients underwent TBE and HRM before Heller myotomy. TBE height and width were recorded at 1 and 5 minutes; HRM measured lower esophageal sphincter mean basal pressure, integrated relaxation pressure (IRP), and mean esophageal body contraction amplitude. Achalasia was classified into types I (25%), II (65%), and III (9.7%). TBE height at 5 minutes was higher for I (median 8 cm; interquartile range 6–12) and II (8 cm; 8–11) than for III (1 cm; 0–7). TBE width at 5 minutes was widest (3 cm; 2–4), narrower in II (2 cm; 2–3), and narrowest in I (1 cm; 0–2), P < 0.001. Volume remaining at 1 and 5 minutes was lower in III (1 m 2 ; 0–16) than I (42 m 2 ; 17–106) and II (39 m 2 ; 15–60), highlighting poorer emptying of I and II. Increasing TBE width correlated with deteriorating morphology and function from III to II to I. Symptoms poorly correlated with TBE and HRM. Prior treatment was associated with less regurgitation, faster emptying, and lower IRP. Although TBE and HRM are correlated in many respects, the wide range of their measurements observed in this study reveals a spectrum of morphology and dysfunction in achalasia that is best characterized by the combination of these studies.